Evolutionary intuitionism : a theory of the origin and nature of moral facts - Zamulinski, Brian Edward, 1951- (McGill-Queen's University Press, 2007)
Evolutionary Intuitionism presents a new evolutionary theory of human morality. Zamulinski explains the evolution of foundational attitudes, whose relationships to acts constitute moral facts. With foundational attitudes and the resulting moral facts in place, he shows how they ground a plausible normative morality, give answers to meta-ethical questions, and provide an account of moral motivation. He explains the nature of moral intuitions and, thus, of our access to the moral facts. He shows that the theory makes confirmed empirical predictions, including the observable variation in moral views. The combination of intuitionism and evolutionary ethics enables Zamulinski to overcome the standard objections to both.